Sex Differences in Treatment Effect of Adjunctive Intra‐Arterial Urokinase After Successful Thrombectomy: A Post Hoc Secondary Analysis of the POST‐UK Randomized Clinical Trial - Xuanyu Chen; Linyu Li; Gaoming Li; Lingyu Zhang; Haoxuan Zhu; Xu Xu; Jinfu Ma; Lilan Wang; Zhixi Wang; Jiayu Li; Qiuyi Yang; Yian Chen; et al. (Journal of the American Heart Association, 2026)
Background Whether adjunct intra‐arterial urokinase has differential effectiveness and safety by sex among patients with acute ischemic stroke who achieve near‐complete to complete reperfusion after endovascular thrombectomy (EVT) remains unknown. Methods This post hoc analysis of the POST‐UK (Adjunctive Intra‐Arterial Urokinase After Successful Endovascular Thrombectomy in Patients With Large‐Vessel Occlusion Stroke) multicenter randomized clinical trial included 534 patients with proximal intracranial large‐vessel occlusion who achieved near‐complete to complete reperfusion after endovascular thrombectomy. Participants were assigned to intra‐arterial urokinase or no adjunct intra‐arterial thrombolysis. The primary effectiveness outcome was 90‐day survival without disability, defined as a modified Rankin Scale score of 0 to 1. Primary safety outcomes were 90‐day all‐cause death and symptomatic intracranial hemorrhage within 48 hours. Results Among 534 participants, 223 were female and 311 were male. The treatment‐by‐sex interaction for the primary outcome was not statistically significant ( P for interaction=0.06). In sex‐stratified analyses, intra‐arterial urokinase showed a potential benefit signal for 90‐day survival without disability among female participants (46.7% versus 32.2%; adjusted risk ratio [RR], 1.47 [95% CI, 1.07–2.02]; P =0.02), whereas no statistically significant difference was observed among male participants (44.1% versus 46.6%; adjusted RR, 0.97 [95% CI, 0.77–1.22]; P =0.79). No statistically significant differences in safety outcomes were observed between treatment groups in either sex, including 90‐day mortality and symptomatic intracranial hemorrhage. Conclusions Adjunct intra‐arterial urokinase after endovascular thrombectomy showed a potential benefit signal for 90‐day disability‐free survival among female participants, without statistically significant differences in male participants or hemorrhagic outcomes across sex subgroups. These findings should be considered hypothesis generating and warrant confirmation in future prospective studies. Registration URL: www.chictr.org.cn ; Unique Identifier: ChiCTR2200065617.